2017
DOI: 10.1002/jbm.a.36240
|View full text |Cite
|
Sign up to set email alerts
|

N,N'‐methylenebis(acrylamide)‐crosslinked poly(acrylic acid) particles as doxorubicin carriers: A comparison between release behavior of physically loaded drug and conjugated drug via acid‐labile hydrazone linkage

Abstract: N,N'-methylenebis(acrylamide) (MBA)-crosslinked poly(acrylic acid) (PAA) particles with low degree of cross-linking were synthesized using distillation precipitation polymerization. Size and size distribution of particles were obtained using dynamic light scattering and field emission scanning electron microscopy( and results showed that microspheres had a narrow size dispersity. Proton nuclear magnetic resonance results indicated that amount of cross-linker in structure of particles is a little more than the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 35 publications
(37 reference statements)
0
19
0
Order By: Relevance
“…Drug release is via ring-opening hydrolysis and thiol exchange [82,83] behavior of doxorubicin that was conjugated onto the structure of nanoparticles. The conjugation was achieved via an acid-labile hydrazone linkage, and the effect of conjugation was compared with the nonconjugated drug [94] (Figure 7). The results of the in vitro investigation revealed that the release of doxorubicin was dependent on the amount of crosslinker.…”
Section: Mechanism Of Cleavage Methods Of Hydrolysis Referencesmentioning
confidence: 99%
“…Drug release is via ring-opening hydrolysis and thiol exchange [82,83] behavior of doxorubicin that was conjugated onto the structure of nanoparticles. The conjugation was achieved via an acid-labile hydrazone linkage, and the effect of conjugation was compared with the nonconjugated drug [94] (Figure 7). The results of the in vitro investigation revealed that the release of doxorubicin was dependent on the amount of crosslinker.…”
Section: Mechanism Of Cleavage Methods Of Hydrolysis Referencesmentioning
confidence: 99%
“…All the above steps were repeated to synthesize fourth generation PAMAM dendrimer (G4.0 which had 32 primary amines per a dendrimer molecule). It is worth to mention that in synthesis of both dendrimers, the amount of reagents varied while their ratio was kept constant as first step. G0.0: (S( a CH 2  a CH 2 )[N( b CH 2  c CH 2 CO d NH 2  e CH 2  f CH 2  g NH 2 ) 2 ) 2 ] 2 ) 2 1 H NMR (CDCl 3 , 400 MHz, δ H (ppm)): 2.53 (4H,s,a); 2.94 (8H,t,b); 2.57 (8H,t,c); 7.90 (4H, bt,d); 3.31 (8H,bq,e); 2.25 (8H,p,f); 1.58 (8H,t,g). 13 C NMR (CDCl 3 , 400 MHz, δ (ppm)): a: 53.3; b: 49.3; c: 51.6; d: 71.3; e: 36.5; f: 32.7. FT‐IR main peaks (υ/cm −1 ): 1640 (CO); two band regions at 3,250 and 3,330 cm −1 due to asymmetrical and symmetrical NH stretch (Modarresi‐Saryazdi, Haddadi‐Asl, & Salami‐Kalajahi, ; Noein, Haddadi‐Asl, & Salami‐Kalajahi, ). G4.0: (S( a CH 2  a CH 2 )[N( b CH 2  c CH 2 CO d NH 2  e CH 2  f CH 2 N( g CH 2  h CH 2 CO i NH j CH 2  k CH 2 N( l CH 2  m CH 2 CO n NH o CH 2  p CH 2 N( q CH 2  r CH 2 CO s NH t CH 2  u CH 2 N( v CH 2  w CH 2  x CONH y CH 2  z CH 2  α NH 2 ) 2 ) 2 ) 2 ) 2 ) 2 ] 2 1 H NMR (CDCl 3 , 400 MHz, δ H (ppm)): 2.70–2.96 (500H, bm, a,b,c,g,h,l,m,q,r,v,w); 8.05–8.15 (124H, bm, d,i,n,s,x); 3.06–3.37 (248H, bm, e,j,o,t,y); 2.48–2.65 (120H, bm, f,k,p,u); 2.18–2.29 (128H, bp, z); 2.41–2.47 (128H, bt, α). FT‐IR main peaks (υ/cm −1 ): 1,650 (CO), 3,265 and 3,330 (NH 2 ) (Nikravan, Haddadi‐Asl, & Salami‐Kalajahi, ). …”
Section: Methodsmentioning
confidence: 99%
“…[29,[175][176][177][178][179][180][181] Dual stimuli-responsive nanogels generally involve a combination of redox-responsive cross-linkers and pH-responsive polymeric matrix as important nanogel constituents. Some of the important examples of pH-responsive polymers are polyacrylamide (PAAm), [182][183][184] poly(acrylic acid) (PAA), [72,185,186] PMAA, [182,[187][188][189][190] poly(2-diethylaminoethyl methacrylate) (PDEAEMA), [191,192] polyethyleneimine, [193][194][195] poly(l-lysine), [196,197] poly(2-vinyl pyridine) (P2VP), [198] poly(Nvinylamine) (PVAm), [199] poly(4-vinyl pyridine) (P4VP), [200,201] and chitosan. [184,202] The pH-and redox-responsive nanogels hold excellent potential and play a diverse role for targeted intracellular release of drugs due to their multidimensional role in response to variation in GSH concentration and pH inside the cellular compartment.…”
Section: Ph-and Redox-responsive Nanogelsmentioning
confidence: 99%